PENGARUH TAX AVOIDANCE DAN DEWAN KOMISARIS INDEPENDEN TERHADAP NILAI PERUSAHAAN DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI - Apriliani, Reski; Muhsin, Muhsin; Ikhsan , Syarbini (Universitas Sarjanawiyata Tamansiswa, 2024)
The aim of this study is to examine and analyze the influence of two independent variables, tax avoidance and independent board of commissioners, on the value of banking companies with audit quality as a moderating variable. This research uses secondary data sourced from the Indonesia Stock Exchange (IDX). The study was conducted to test several predetermined hypotheses. Specifically, in the IDX, 14 banking companies were observed for this research. The study period spans four years (2020-2023). Panel data regression analysis was used to test the validity of the hypotheses with the help of Eviews 12 software. Based on the results of this study, tax avoidance and the independent board of commissioners have a positive effect on the value of the company. Audit quality is unable to moderate the effect of tax avoidance on the value of the company. However, audit quality significantly moderates the effect of the independent board of commissioners on the value of the company.